"We Don’t Need No Ordination": Analysis of the Discourse on Women’s Ordination in Latvian Online Media from 1999 to 2022 - Zavelis, Emīls (Occasional papers on religion in Eastern Europe, 2024)
This paper analyzes the discourse on women's ordination in the Evangelical Lutheran Church of Latvia (ELCL) as represented in Latvian online media from 1999 to 2022. The study combines qualitative and quantitative methodologies to examine the argumentative strategies employed by different discourse producers. The findings reveal significant differences in the use of gender equality concepts and other argumentative patterns between those in favor and those against women's ordination. These differences can be attributed to the distinct sociocultural contexts and epistemic grounds of the ELCL and the Evangelical Lutheran Church of Latvia Worldwide (ELCLW). The paper highlights the need for a deeper understanding of the sociopolitical and cultural factors that shape the discourse on women's ordination in religious communities.